2017
DOI: 10.1007/s40979-017-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the profiles of a plagiarist: a study of abstracts submitted to an international interdisciplinary conference

Abstract: Much of the current literature on plagiarism focuses on students, attempting to understand how students view the concept of plagiarism, the best ways to prevent it, and the impact of collaboration on the concept of original authorship. In this article, we look at the role of plagiarism in 761 conference abstracts written by graduate students, early-to late-career faculty, and industry representatives, representing institutions from nearly 70 countries. These abstracts were submitted for participation in an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Indeed, while the presence of plagiarism in scientific publications has been well-documented, this type of misbehavior in conference meetings has received limited attention. One early study of conference submissions reported that self-plagiarism, rather than plagiarism, was the basis for most of the textual overlap reported [ 40 ]; another study of actual conference papers revealed roughly the opposite outcome [ 41 ]. Two other studies of papers presented at conferences in the field of Management have reported considerable amounts of textual overlap [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while the presence of plagiarism in scientific publications has been well-documented, this type of misbehavior in conference meetings has received limited attention. One early study of conference submissions reported that self-plagiarism, rather than plagiarism, was the basis for most of the textual overlap reported [ 40 ]; another study of actual conference papers revealed roughly the opposite outcome [ 41 ]. Two other studies of papers presented at conferences in the field of Management have reported considerable amounts of textual overlap [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study was grounded by the informal observation that while guidance on research integrity is stated by most scholarly journals [ 44 ], ethical standards for scientific conferences (e.g., cautioning authors against plagiarism) are vague or sometimes not explicitly stated but only implied upon submission of scientific findings. Moreover, with some exceptions [ 41 , 45 ], this form of scientific exchange does not appear to be as heavily screened for integrity issues as journal papers are [ 12 ]. In view of growing concerns about the integrity of the scientific record and the need for transparency in all aspects of research, we attempted to estimate the extent of text overlap in a large sample of conference abstracts spanning several meetings across various disciplines in the biomedical sciences.…”
Section: Introductionmentioning
confidence: 99%
“…"Plagiarism, collusion and other forms of academic misconduct have always been a regrettable but unavoidable aspect of academic existence" (Carroll & Appleton, 2001, p.6). However, plagiarism is not an easy concept to identify when considering various profoundly contextualized authorship and textual practices in a variety of domains and organizations (Hodges, Bickham, Schmidt & Seawright, 2017). Since textual regulations of approved submissions have changed over time and they show varies from context to context, even within the same social community, it is getting more problematic to define plagiarism (Hodges et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, plagiarism is not an easy concept to identify when considering various profoundly contextualized authorship and textual practices in a variety of domains and organizations (Hodges, Bickham, Schmidt & Seawright, 2017). Since textual regulations of approved submissions have changed over time and they show varies from context to context, even within the same social community, it is getting more problematic to define plagiarism (Hodges et al, 2017). Coughlin (2015) states that defining the concept of plagiarism in a clear way is not the core of the problem, but it is constructing concurrence and having learners and lecturers adopt the definition and implement necessary disciplinary and educational steps with a sensible and sustainable manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation